Fighting for their survival: The International Rhino Foundation ensures the survival of rhinos trhough strategic partnerships, targeted protection, and scientifically sound interventions - Whitlatch for IRF, Christopher (Pachyderm, 2021)
The International Rhino Foundation (IRF), based in the United States operates on-the-ground programmes in Africa and Asia where rhinos live in the wild, supporting viable populations of the five remaining rhino species and the communities that coexist with them. Through grants and field programmes, IRF has funded rhino conservation efforts in 10 countries, focusing on scientific research, anti-poaching, habitat conservation, captive breeding, environmental education, and demand reduction strategies. Over the last decade more than $20 million has been invested in rhino conservation. The organization was founded by concerned individuals in response to intense poaching of Zimbabwe’s black rhinos in the early 1990s. IRF with supporters and partners helped to virtually eliminate the threat and stabilize the population there. To this day, we support conservation programmes in Zimbabwe and IRF has expanded to support all five species of rhinos. IRF prioritizes collaboration. Through a network of hundreds of conservation organizations, private foundations, corporations, government agencies and individuals all over the world, we achieve common goals for rhinos together. We are Team Rhino. IRF listens to local communities living in close proximity to rhino populations. Working together, we participate in mutually beneficial partnerships through wildlife conservation. A key objective is to build a unified front to save rhinos by engaging and activating the many people around the world who are as concerned as we are about the rhino. Our global team of rhino conservationists is calling for an end to rhino poaching and sharing the plight of the rhino with others.